﻿Determination of TLC fingerprint biomarker of Ipomoea batatas (L.) Lam leaves extracted with ethanol and its potential as antihyperglycemic agent - Putu Sanna Yustiantara; Ni Kadek Warditiani; Pande Made Nova Armita Sari; Ni Luh Kade Arman Anita Dewi; Yan Ramona; I Made Jawi; I Made Agus Gelgel Wirasuta (Pensoft Publishers, 2021)
Antihyperglycemic activity of Ipomoea batatas (L.) leaves has been studied for years. As many naturally found varieties of such plant species have been used as herbal medicines, there is a need to establish a fingerprint biomarker standardization method. Our research combined TLC fingerprints and chemometric analysis to determine biomarkers in leaf ethanol extract of Ipomoea batatas (L.) (EIBL). We predicted the main constituents of anthocyanin glycosides and their acylated derivates in the leaf ethanol extract of such plants using ESI-MS. The EIBL that contained identified biomarkers has succeeded in providing an antihyperglycemic effect in experimental using STZ-induced rats. This study also found a linear correlation between doses of flavonoid derivates as antioxidant agents with their antihyperglycemic activities. Therefore, this biomarker information can be used as a model to predict the dose-responses of the antihyperglycemic activities produced by other leaf ethanol extracts of I. batatas.